Wi-Fly: Widespread Opportunistic Connectivity via Commercial Air Transport - Ahmad, Talal; Chandra, Ranveer; Kapoor, Ashish; Horvitz, Eric; Daum, Michael (HotNets-XVI: Proceedings of the 16th ACM Workshop on Hot Topics in Networks (ACM HotNets), 2017)
More than half of the world's population face barriers in accessing the Internet. A recent ITU study estimates that 2.6 billion people cannot afford connectivity and that 3.8 billion do not have access. Recent proposals for providing low-cost connectivity include fielding of drones and long-lasting balloons in the stratosphere. We propose a more economical alternative, which we refer to as Wi-Fly, that leverages existing commercial planes to provide Internet connectivity to remote regions. In Wi-Fly we enable communication between a lightweight Wi-Fi device on commercial planes and ground stations, resulting in connectivity in regions that do not otherwise have low-cost Internet connectivity. Wi-Fly leverages existing ADS-B signals from planes as a control channel to ensure that there is a strong link from the plane to the ground, and that the stations intelligently wake up and associate to the appropriate AP. For our experimentation, we have customized two airplanes to conduct measurements. Through empirical experiments with test flights and simulations, we show that Wi-Fly and its extensions have the potential to provide connectivity to the most remote regions of the world at a significantly lower cost than existing alternatives.